Culicoides biting midges among cattle in France: be wary of data in the literature - Millot, Christine; Hadj-Henni, Leila; Augot, Denis (Frontiers in Veterinary Science, 2024)
Culicoides are vectors that can transmit many different pathogens to mammals — including humans, and domestic and wild animals — and birds. In order to take preventive measures against any vector-borne disease, it is important to gather information on both the host and vector species. Culicoides species are mainly mammalophilic, ornithophilic or ornithophilic/mammalophilic, but females have also been found to occasionally feed on engorged insects. A recent systematic review based on three groups of key words investigated Culicoides on farms, and asserted that 92 species (including four not present species) have been reported among cattle in mainland France and Corsica. We have re-evaluated the presence of Culicoides species in cattle in France using the same data of the review. Our data show that only 18 species are reported among cattle. Furthermore, our research used molecular and indirect investigations to analyse Culicoides species that had been feeding on cattle. Our results demonstrate that 45 species feed on cattle out of 92 species present in France. The paper discusses the relevance of data in the literature when investigating hosts of Culicoides species.